Opportunities to strengthen Africa’s efforts to track national-level climate adaptation - Nowak, Andreea C.; Njuguna, Lucy; Ramirez Villegas, Julian; Reidsma, Pytrik; Crumpler, Krystal; Rosenstock, Todd S (Nature Portfolio, 2024)
Abstract Tracking progress towards the Global Goal on Adaptation requires documentation of countries’ intentions, against which future progress can be measured. The extent to which existing national policy documents provide adequate baselines is unclear. We evaluated the adequacy of African Nationally Determined Contributions (NDCs) ( N = 53) and National Adaptation Plans (NAPs) ( N = 15) against three criteria—coverage, consistency and robustness—mapped to the adaptation cycle. Fifty-three percent of NAPs and 8% of NDCs cover all elements needed for providing sufficient baselines for tracking adaptation progress. Only 40% and 9% of the NAPs and NDCs, respectively, provide consistent links between climate risk assessment, planning, implementation and tracking. No document provided fully robust indicators to operationalize tracking. Notable efforts towards adequacy exist, especially in NAPs. The findings illustrate continental-scale advances and shortcomings for tracking progress, and emphasize opportunities in upcoming NDC revisions and NAP processes to enhance their coverage, consistency and robustness for future adaptation tracking.